Immunoglobulin and CD8+ T-cell distribution in histologically distinctive tonsils of individuals with tonsillar focal infection. (March 2014) - Meng, Hong-xue; Ohe, Rintaro; Li, Hui-ning; Yang, Su-ran; Kabasawa, Takanobu; Kato, Tomoya; Zhang, Lei; Ohtake, Hiroya; Ishida, Akihiro; Ohta, Nobuo; Jin, Xiao-ming; Kakehata, Seiji; et al.
Abstract Conclusion: This study demonstrated that the common immunological mechanism, which involves aberration of immunoglobulin and T-cell distribution in histologically distinctive tonsils, may be associated with the pathogenesis of tonsillar focal infection. Objectives: Tonsillar focal infection comprises a group of relatively common diseases combined with chronic tonsillar infection, is associated with unusual immune responses in tonsils, and may cause lesions in another distant target organ. This study aimed to investigate the distribution of inflammatory T cells and T-cell regulatory elements, such as programmed cell death-1 (PD-1) and Fork head box protein 3 (Foxp3), immunoglobulin production, and histological characteristics in tonsils from patients with tonsillar focal infection. Methods: Immunohistochemistry and reverse transcription-polymerase chain reaction (PCR) were used to compare the expression of CD8+ T cells, immunoglobulins, and cytokines associated with immunoglobulin production in the tonsils of patients with IgA nephropathy (IgAN), palmoplantar pustulosis (PPP), rheumatoid arthritis (RA), and chronic tonsillitis. Results: The overexpression of CD8+ T cells combined with decreased expression of Foxp3 and PD-1 and the aberration of immunoglobulin production, which may be due to the elevated expression of activation-induced deaminase (AID), B-cell-activating factor of the TNF family (BAFF), supporting isotype switching, and B-cell survival in the histologically distinctive tonsils.